2007
DOI: 10.1093/cvr/cvm087
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cholesteryl ester transfer protein overexpression and inhibition on reverse cholesterol transport

Abstract: Both increased (mice study) and decreased (hamster study) CETP activity could result in enhanced RCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 29 publications
4
53
0
1
Order By: Relevance
“…This method utilizes J774 macrophages labeled in vitro with 3 H-cholesterol and oxidized LDL and monitors the movement of 3 H-tracer into cholesterol and bile acid pools in plasma, liver, and feces following injection into animals. This method has been used in hamsters to examine the effects of several pharmacotherapies on macrophageto-feces RCT, including liver X receptor activation ( 22 ) and CETP inhibition with torcetrapib ( 29 ). To comprehensively assess the effects of a pharmacological intervention on cholesterol handling and excretion, it is important not only to study macrophage-to-feces RCT but also to take into account the bulk movement of cholesterol mass within lipoproteins and in the fecal compartment.…”
Section: Discussionmentioning
confidence: 99%
“…This method utilizes J774 macrophages labeled in vitro with 3 H-cholesterol and oxidized LDL and monitors the movement of 3 H-tracer into cholesterol and bile acid pools in plasma, liver, and feces following injection into animals. This method has been used in hamsters to examine the effects of several pharmacotherapies on macrophageto-feces RCT, including liver X receptor activation ( 22 ) and CETP inhibition with torcetrapib ( 29 ). To comprehensively assess the effects of a pharmacological intervention on cholesterol handling and excretion, it is important not only to study macrophage-to-feces RCT but also to take into account the bulk movement of cholesterol mass within lipoproteins and in the fecal compartment.…”
Section: Discussionmentioning
confidence: 99%
“…However, animal studies that have been undertaken to demonstrate a direct contribution of CETP in accelerating macrophage to feces RCT have led to contradictory results (14 -18). Studies that reported a role of CETP in RCT have used either [ 3 H]cholesterol-labeled RAW264.7 or J774 cells in their in vivo RCT assay (14,15). These macrophage cell lines do not produce APOE (35).…”
Section: Discussionmentioning
confidence: 99%
“…A kinetic study in humans notably suggested that most of the CE output to liver occurred through APOB-containing lipoproteins, with very little from HDL (13). These data, which favor a role of CETP in promoting RCT, are supported by studies performed in mice overexpressing CETP by adenoviral-or adenoassociated virus-mediated gene transfer (14,15). However, a lack of effect of CETP in modulating RCT in CETP-expressing mice has also been reported and is in contradiction with the latter findings (16 -18).…”
mentioning
confidence: 93%
“…212 The treatment of hamsters with torcetrapib increased the mobilization of radiolabeled cholesterol from peritoneal macrophages into plasma HDL and subsequent excretion into stool. 213,214 Dalcetrapib: Results of a phase IIb study comparing different doses of dalcetrapib in dyslipidemic patients treated with pravastatin (40 mg/day) indicated a positive effect of dalcetrapib on ABCA1-and SR-BI-mediated cellular cholesterol removal. 215 Likewise, in the dal-ACUTE study that enrolled 300 patients who had a recent ACS, dalcetrapib at a daily dose of 600 mg enhanced the capacity of apoB-depleted plasma to elicit non-ABCA1-specific cholesterol efflux from macrophage foam cells, which was related to changes in apoA-I and HDL-cholesterol levels.…”
Section: Fibratesmentioning
confidence: 99%